Can Emission Trading Scheme Improve Carbon Emission Performance? Evidence From China - Yuhua Zheng; Xiaoyang Sun; Chenyu Zhang; Daojuan Wang; Ju Mao (Frontiers in Energy Research, 2021)
This paper explores the effect of China’s emission trading scheme (ETS) pilot policy implemented during 2013-2014 on carbon emission performance. Adopting the Difference-in-Difference (DID) model, we find that: 1) China’s ETS pilot policy can significantly improve the carbon emission performance of listed companies in the pilot provinces. 2) The heterogeneity analysis shows that the carbon emission performance of listed companies in the eastern coastal pilot areas has improved significantly, which is not significant in the central and western pilot areas. 3) We find that China’s ETS pilot policy can significantly improve innovation capabilities of listed companies, suggesting that innovation is a channel for the impact of the China’s ETS pilot policy on carbon emission performance in the pilot provinces. Overall, our study shows that ETS pilot policy has played a governance role in China and improved carbon emission performance. We further highlight some important policy implications with respect to helping companies save energy and reduce emissions, and promoting the further improvement of China’s ETS pilot policy.